Efektivitas Implementasi E-courtBerdasarkan PeraturanMahkamah Agung Nomor 1 Tahun 2019 Tentang AdministrasiPerkara dan Persidangan di Pengadilan Secara Elektronik - ulfa, maratul (Al-Hukkam: Journal of Islamic Family Law, 2022)
The implementation of e-court a breakthrough and innovation from the electronic justice system which was formed from PERMA Number 3 of 2018 over time it was updated to PERMA1of2019whichregulatese-filling(registration),e-payment(payments),e-summons (summons), and e-litigation (trial), these are as apllied in the Kajen Religious Court. This study aims to determine the effectiveness of e-court implementation in the Kajen Religious Court. This research is a qualitative research which tends to be an analysis in accordance withthefactsinthefieldwithanempricaljuridicalapproach.Primarydataweretakenfrom interviews with e-court officers,judges,clerks,e-court litigants,manual litigants and advocates as well as the authors made observations in the court environment. Kajen’s religion secondary data used were books, journals, previous research related to the same theme. The results of this study are to measure the effectiveness of the law and to find out thesettlementofcasesattheKajenReligiouscourtwiththeprinciplesofasimple,fast,and low cost trial. The reality is that the implementation of the e-court at the Kajen religious court iss quite good, but there are stil lmany things that need to be improved from the factors that hinder the implementation of the e-court as seen from the access to payments via transfer to the bank which is still error and other obstacles. Judging from the analysis of the efektiviness of the law, the implementation of e-court has not been achieved optimally which is a accepted by the people who arelitigating.